M22 Does telephoning patients before the difficult-to-treat asthma clinic improve attendance?. (15th November 2017) - Oliveira, S; Robinson, R; Mault, S; McDonough, B; James, H; Joplin, H; Jones, G; Blakey, J; Burhan, H
Abstract : Aims: To assess the use of telephone reminders in a difficult-to-treat asthma service on: 1) clinic attendance rates 2) the prevalence of poor concordance Background: Non attendance at clinics leads to increased pressure on NHS resources and cost the NHS £3225 million in 2012–2013. Our trust has an opt-in appointment text message reminder service – despite which, the did-not-attend (DNA) rate at our tertiary asthma clinic was ≥20% in 2016. It is known that up to 30% of patients attending tertiary asthma services have poor adherence with their asthma medication. 1 We were interested in establishing whether directly telephoning patients prior to review would allow us to impact DNA rate and simultaneously identify non-concordant individuals that might be redirected to specialist pharmacy input prior to clinical review. Methods: During a 3 month period [Feb-Apr 2017] we telephoned patients≥1 week prior to their scheduled appointment – in total 3 attempts were made to contact an individual. During successful contacts express permission was sought to access electronic prescription fulfilment data. Results: Successful contact was made with 53.4% [66/126] patients – 41 did not answer, 19 had no valid contact details. The majority of those contacted [54/66] agreed to an adherence check but only n=37 had been registered on the electronic prescription fulfilment system, of these 51% [19/37] had an asthma medication pick-up rate <80%. Of those successfully contacted n=64/66 attended their appointment which compared favourably to the overall DNA rate during the same period in 2016 [3.0% vs 17.5%; p=<0.05]. Although we managed to perform a compliance check on less than a third of the total cohort [37/122], our telephone system allowed ≥1 in 6 patients [19/122]to be directed to a dedicated specialist pharmacist led clinics (focussing on optimising concordance/education) thus creating additional capacity in our difficult-to-treat asthma service. Conclusion: Telephoning patients prior to clinic was associated with a substantial reduction in DNAs, and identified individuals that could benefit from a targeted intervention around concordance. The health economics of the intervention need further evaluation. Reference: . Robinsonet al. Systematic assessment of difficult-to-treat asthma. ERJ2003, September;22(3):478–83.